(untitled) (Ius Novum, 2021)
The article attempts to establish the basic relationship between the type of prohibited act and its varieties and the appropriateness of using the speciality rule as a mechanism to reduce the multiplicity of assessments in criminal law. The deliberations were based on the knowledge of the structure of the so-called conjugated norms, determinants of the rules of the derivational concept of interpretation of the law in connection with the horizontal interpretation of the legal text, the technique of editing the texts of legal acts and in the spirit of the Poznań–Szczecin school in the theory of law and the conceptual apparatus developed by it. Against this background, it was established that each typifying provision of the specific part of the penal code expresses its own sanctioned and sanctioning norm, as a central framework provision. In this sense, the types are modified by the central regulations that define the basic types of prohibited acts. These modifiers are essential components of the sanctioned norm reproduced in the provision typifying the basic type, which occurs at the reconstructive phase of interpretation of the law. As a result, modified types do not modify anything at the level of the sanctioning norms and remain in a relationship of exclusion with the provisions defining the basic type of a prohibited act. There is no collision between the sanctioning norms reconstructed from the basic type and its varieties. In determining the relationship between the basic type and its varieties, it is not appropriate to resort to the speciality rule. The speciality rule is not at all a rule excluding multiple assessments in criminal law.